Recombination plasticity in response to temperature variation in reptiles - González-Rodelas, Laura; Marín-García, Cristina; Romero, Clara; Pujol, Gala; Marín-Gual, Laia; Kratochvíl, Lukáš; Ruiz-Herrera, Aurora (PLoS genetics, 2025)
The survival of species depends on their ability to adapt to environmental changes. While organisms are known to activate common transcriptional pathways in response to temperature variations, the impact of temperature on recombination, a key source of genetic variability, remains largely unexplored. Previous studies in model species have shown that the frequency of recombination during meiotic prophase I can be influenced by extreme temperatures. Yet, it remains unclear whether this effect is also conserved in non-model vertebrates. In this study, we investigated the effect of temperature on recombination in the Guibé's ground gecko (Paroedura guibeae), an ectotherm species. We analyzed the formation of double-strand breaks (DSBs) and crossovers (COs) by immunolocalizing the meiotic proteins involved in these processes. Furthermore, we determined the frequency and chromosomal location of COs and the levels of CO interference (COI). Our findings show the presence of hyper-COs spermatocytes in individuals exposed to both high and low temperatures. Notably, this significant increase in COs was associated with a decrease in chromosome axis lengths and elevated levels of meiotic DSBs in later stages of prophase I. In conclusion, our results provide new insights into the effects of environmental temperatures on meiotic recombination in ectothermic species, underscoring the intricate interplay between environmental factors and genetic processes.
Keywords: rekombinace genetická; Crossing Over, Genetic; Spermatocytes; Temperature; DNA Breaks, Double-Stranded; Recombination, Genetic; dvouřetězcové zlomy DNA; ještěři; spermatocyty; teplota; Meiotic Prophase I; Meiosis; zvířata; meióza; Male; crossing over (genetika); Lizards; Animals; mužské pohlaví; profáze meiózy I